Reactions of carboline. Issue 4 (1997) - Dardonville Dardonville, Christophe Christophe; Virelizier Virelizier, Henri Henri; Boivin Boivin, Jean Jean; Jankowski Jankowski, Christopher K. Christopher K.
Abstract : The reactions of carboline under various oxidative conditions are reported. The soft aerobic radiolysis, hydroxylation and rearrangement transformations are studied using isotopic labelling and GC–MS techniques.